THE DIDACTIC PROBLEMS IN THE SECONDARY SCHOOL AS THE AGENT OF THE CHANGE IN TEACHER TRAINING - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2010)
The 2009–2010 year research data has shown that didactic objectives, content, methods, assessment of the organization is defined as the main didactic problems in the secondary school. Many teachers still continue to work on the educational paradigm conceptual share despite the paradigm of free education in law is established nearly 20 years. The research findings identified didactic problems in teachers’ and students’ approach. It ensures the assumptions for modelling the directions of teacher trainings. It is important to highlight that student themselves are not focused on the formulation of educational objectives, reflection on the school / learning process and evaluation on their achievement. The identification of the didactic problems underline that teachers are formal documents oriented and sometimes rewrite from them the formulated educational objectives. This affects the whole system of didactic modelling. This complicates the search for the harmony of objectives, content, methods, forms, background, and education stakeholders’ in free educational paradigm and conceptual sphere as well as become a guide for development of teacher training.